Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Terhadap Pemahaman Konsep Matematis Peserta Didik Kelas VIII SMPN 15 Padang - SUMIARTI . (Jurnal Edukasi dan Penelitian Matematika, 2020)
Abstract  Understanding mathematical concepts is one of the goals that must be mastered by students in learning mathematics. the reality of understanding the mathematical concepts of students in class VIII SMP Negeri 15 Padang is still low. In addition, students are less active in the learning process. Efforts that can be made to improve students' mathematical understanding of concepts are by applying the Two Stay Two Stray cooperative learning model. This study aims to analyze and describe how the learning activities of students who applied the TSTS model and whether understanding mathematical concepts of students who learn by using the Two Stay Two Stray cooperative learning model is better than understanding mathematical concepts Learners who learn by using conventional learning models in class VIII of SMP Negeri 15 Padang. This type of research is a quasi-experimental design with Static Group Design. The research instrument was an observation sheet of students' activities and the final test was in the form of an essay which was analyzed using a non-parametric statistical test, the Mann-Whitney test. Based on statistical test analysis obtained P-value of 0.0078 smaller than the real level of 0.05, then Ho is rejected. That is, understanding mathematical concepts of students learning by using the Two Stay Two Stray cooperative learning model is better than understanding mathematical concepts of students learning by using conventional learning models in class VIII of SMP Negeri 15 Padang. Keywords : Understanding Mathematical Concepts, Two Stay Two Stray Cooperative Learning Models, Conventional Learning Models